新規高血圧・糖尿病性腎症併発マウスモデル(デオキシコルチコステロン酢酸塩・食塩水投与片腎摘出KKAyマウス)におけるPDE4, 5阻害薬の病態改善効果 - 仁尾, 泰徳 (日本薬理学会年会要旨集, 2021)
Diabetic nephropathy (DN) is a leading cause of end-stage renal disease (ESRD). Hypertension increases kidney stress, which deteriorates function, and leads to peripheral renal vascular resistance. Long-term hypoperfusion promotes interstitial fibrosis and glomerular sclerosis, resulting in nephrosclerosis. Although hypertension and DN are frequent ESRD complications, relevant animal models remain unavailable. We generated a deoxycorticosterone acetate (DOCA)-salt hypertensive uni-nephrectomized (UNx) KKAy mouse model demonstrating hypertension, hyperglycemia, cardiac hypertrophy, kidney failure, increased urinary albumin creatinine ratio (UACR), and increased renal PDE4D and cardiac PDE5A mRNA levels. We hypothesized that the novel PDE4 selective inhibitor, compound A, and PDE5 inhibitor, sildenafil, exhibit nephroprotective and cardioprotective effects in this new model. Compound A, sildenafil, and the angiotensin II receptor blocker, irbesartan, significantly reduced ventricular hypertrophy and pleural effusion volume. Meanwhile, compound A and sildenafil significantly suppressed the UACR, urinary kidney injury molecule-1, and monocyte chemoattractant protein-1 levels, as well as that of renal pro-fibrotic marker mRNAs, including collagen 1A1, fibronectin, and transforming growth factor-beta (TGF-β). Moreover, compound A significantly suppressed TGF-β-induced pro-fibrotic mRNA expression in vitro in all major kidney lesions, including within the glomerular mesangial region, podocytes, and epithelial region. Hence, PDE4 and PDE5 inhibitors may be promising treatments, in combination with irbesartan, for DN with hypertension as they demonstrate complementary mechanisms.